Optimalisasi Performa Lompat Jauh Melalui Pembinaan Teknik, Fisik, Dan Konsistensi Gerak Atlet : Penelitian - Daniel Deach Marponiroha Manurung; Dhesty Zaina Putri; Dicky Edwar Daulay; Rezi Alghifary; Riesya Salsabila; Yan Indra Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine strategies for optimizing long jump performance through the integration of technical training, physical conditioning, and movement consistency using a literature review approach. The analysis includes Sinta-indexed national journals and relevant scientific books published within the last five years. The findings indicate that each phase of the long jump—approach run, final stride, take-off, flight, and landing—requires proper technical execution supported by physical components such as strength, speed, power, and flexibility. Moreover, consistent movement patterns play a crucial role in maintaining stable performance, particularly in the precision of approach steps and the effectiveness of take-off. Literature synthesis highlights that these three aspects cannot be developed separately but must be trained simultaneously through a holistic training approach. The integration of technical mastery, physical conditioning, and movement consistency has been shown to improve training effectiveness and optimize jump performance. This study provides valuable insights for coaches, athletes, and scholars as a foundation for designing more comprehensive and sustainable training programs to enhance long jump achievement.